2018
DOI: 10.1080/21645515.2018.1520582
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B vaccination among 1997-2011 birth cohorts in rural China: the potential for further catch-up vaccination and factors associated with infant coverage rates

Abstract: Hepatitis B vaccination rates in China have recently increased. This study aimed to investigate infant vaccination coverage for birth cohorts from 1997 to 2011 in rural regions and to assess catch-up vaccination potential. We used questionnaire-based interviews from a cross-section of 6,529 individuals from seven provinces. Logistic regression analyses were used to model two measures of infant vaccination status, namely, birth dose within 24 hours and three doses within the first year of life. During interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
3
4
0
Order By: Relevance
“…Moreover, an association has been observed between knowledge and attitudes, since respondents who very worried that their children could have rotavirus gastroenteritis were those who have heard about rotavirus infection. This finding is in keeping with findings of previous studies that showed that vaccination might be accepted in those more knowledgeable [26,32,33]. These findings indicate that providing specific vaccine-related knowledge may help to change their attitudes.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, an association has been observed between knowledge and attitudes, since respondents who very worried that their children could have rotavirus gastroenteritis were those who have heard about rotavirus infection. This finding is in keeping with findings of previous studies that showed that vaccination might be accepted in those more knowledgeable [26,32,33]. These findings indicate that providing specific vaccine-related knowledge may help to change their attitudes.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that, even in a province that could be considered to be uniformly developed, a small difference in economic development could impact on the utilization of a vaccination service. The frequency of sessions also played an important role in the completeness of Hep B, which was consistent with the previous studies [7,38]. It was demonstrated that frequent sessions and extending the service time were the most beneficial interventions for working mothers through improving the convenience and accessibility of the service and enhancing mothers’ compliance with the vaccination schedule [39,40,41,42].…”
Section: Discussionsupporting
confidence: 86%
“…Generally, the coverage of each dose of Hep B improved from the birth cohort 1999 to the birth cohort 2017 and had maintained the goal of 90% since the birth cohort 2004. This trend was similar to that at the national level [2,7,10]. The coverage of the three-dose Hep B tripled from 30.0% for children born in 1992 to 91% for children born in 2012 at the national level [2].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The prevalence of HBV infection in rural China has been reported to be higher than that in urban areas [42,43]. Moreover, the hepatitis B vaccine coverage rate and the prevalence of vaccine-mediated immunity in rural areas are also low [35,36,44,45].…”
Section: Discussionmentioning
confidence: 99%